Tool-Use Model to Reproduce the Goal Situations Considering Relationship Among Tools, Objects, Actions and Effects Using Multimodal Deep Neural Networks - Saito, Namiko; Ogata, Tetsuya; Mori, Hiroki; Murata, Shingo; Sugano, Shigeki (Frontiers in Robotics and AI, 2021)
We propose a tool-use model that enables a robot to act toward a provided goal. It is important to consider features of the four factors; tools, objects actions and effects at the same time because they are related each other and one factor can influence the others. The tool-use model is constructed from deep neural networks (DNNs) using multimodal sensorimotor data; image, force and joint angle information. To allow the robot to learn tool-use, we collect training data by controlling the robot to perform various object operations using several tools with multiple actions that leads different effects. Then the tool-use model is thereby trained and learns sensorimotor coordination and acquires relationships among tools, objects, actions and effects in its latent space. We can give the robot a task goal by providing an image showing the target placement and orientation of the object. Using the goal image with the tool-use model, the robot detects the features of tools and objects, and determines how to act to reproduce the target effects automatically. Then the robot generates actions adjusting to the real time situations even though the tools and objects are unknown and more complicated than trained ones, with which it is difficult to complete the task just by repeat the trained actions.